Macroeconomic news, announcements, and stock market jump intensity dynamics - José Gonzalo Rangel (Banco de México, 2009)
This paper examines the effect of macroeconomic releases on stock market volatility through a Poisson-Gaussian-GARCH process with time varying jump intensity, which is allowed to respond to such information. It is found that the day of the announcement, per se, has little impact on jump intensities. Employment releases are an exception. However, when macroeconomic surprises are considered, inflation shocks show persistent effects while monetary policy and employment shocks show only short-lived effects. Also, the jump intensity responds asymmetrically to macroeconomic shocks. Evidence that macroeconomic variables are relevant to explain jump dynamics and improve volatility forecasts on event days is provided.
Keywords: C22; G14; 330; conditional jump intensity; conditional volatility; macroeconomic announcements